Acute gastroenteritis: Chlorophyllum molybdites mushroom poisoning—a differential diagnosis to consider and a review of literature - Zakaria, Nor Fadhlina; Mohamed Hatta, Siti Nabihah (Ministry of Health, Brunei Darussalam, 2022)
Mushrooms are a very versatile cooking ingredient as they are loved for their delicious and meat-like texture. In the South-East Asian region, most tropical countries have a wide range of mushrooms in all shapes and sizes; they can be edible, have medicinal and industrial values, and some are even poisonous. Mushroom poisoning is regularly mistaken for common food poisoning presented with acute gastroenteritis symptoms. To date, in Malaysia, for instance, less than 100 cases of Chlorophyllum molybdites poisoning were reported, mostly mimicking acute gastroenteritis symptoms of diarrhoea, nausea, and abdominal pain. We report successful management of a couple who were diagnosed to have Chlorophyllum molybdites poisoning.